AN ANALYSIS OF SLANG LANGUAGE IN SONG LYRICS USED BY “AVRIL LAVIGNE” - saputri, wulan sari (Journal of English Language Teaching and Literature (JELTL), 2021)
The objective of this study are to find out slang language in song lyrics used by Avril Lavigne to find out the meaning of the slang language in song lyrics used by Avril Lavigne. This study concern with the analysis slang language in Avril Lavigne song lyrics. This study is descriptive qualitative. The data classified based on word formation processes according to Yule’s theory (2010). In the data analysis the writer applied qualitative. Method and focused on content analysis. The analysis started on January 2020 until July 2020. This final project based on a study which attemps to find slang language in Avril Lavigne Song lyrics, and know the types slang language used in Avril Lavigne song lyrics. The results of study, the slang language words of the song Avril Lavigne also influenced by some of word formation, there are twelve type of slang word formation. There are Coinage, Compounding, Clipping, Blending, Borrowing, Back formation, Acronyms, Multiple process, Affixes (Prefix, Infix, Suffix). There are four types of slang language were identified based on the findings used in Avril Lavigne song lyrics found 4 clipping, 10 blending, 2 compounding, and 1 Back formation . Based on the research, the process of blending is the most common process that is found in Avril Lavigne song.